Exploring the role of virtual reality in military decision training - Harris, D. J.; Arthur, T.; Kearse, J.; Olonilua, M.; Hassan, E. K.; De Burgh, T. C.; Wilson, M. R.; Vine, S. J. (Frontiers in Virtual Reality, 2023)
Simulation methods, including physical synthetic environments, already play a substantial role in human skills training in many industries. One example is their application to developing situational awareness and judgemental skills in defence and security personnel. The rapid development of virtual reality technologies has provided a new opportunity for performing this type of training, but before VR can be adopted as part of mandatory training it should be subjected to rigorous tests of its suitability and effectiveness. In this work, we adopted established methods for testing the fidelity and validity of simulated environments to compare three different methods of training use-of-force decision making. Thirty-nine dismounted close combat troops from the UK’s Royal Air Force completed shoot/don’t-shoot judgemental tasks in: i) live fire; ii) virtual reality; and iii) 2D video simulation conditions. A range of shooting accuracy and decision-making metrics were recorded from all three environments. The results showed that 2D video simulation posed little decision-making challenge during training. Decision-making performance across live fire and virtual reality simulations was comparable but the two may offer slightly different, and perhaps complementary, methods of training judgemental skills. Different types of simulation should, therefore, be selected carefully to address the exact training need.